PENERAPAN PROBLEM-BASED LEARNING BERBASIS PERMAINAN “ULAR TANGGA” DALAM MENINGKATKAN PEMAHAMAN MATEMATIS PESERTA DIDIK SEKOLAH DASAR DI KOTA BANDUNG - Dini Nurhidayah (STKIP Subang, 2023)
This research is undermined by the fact that the level of mathematical understanding in class 3B SDN 096 Sarijadi Selatan, Bandung for the academic year 2022/2023 is still low and, in particular, has not properly understood the concept of the materials taught. The use of the problem-based learning (PBL) model packed into the game of thematic snake staircase (ULTAMET) becomes one of the options to enhance the mathematical understanding of the learners. Problem-based learning, packed into the game of snake staircase,